EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN ROUND ROBIN BRAINSTORMING DALAM MENINGKATKAN HASIL BELAJAR GEOGRAFI KELAS X DI SMA PERTIWI 1 PADANG - Suryani Harahap, Eka; Nofrion (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low geography learning outcomes of grade X students at SMA Pertiwi 1 Padang. Learning tends to be teacher-centered, students tend to be passive in learning activities so that students easily feel bored and their concentration levels decrease. The purpose of this study is to determine the effectiveness of using the Round Robin Brainstorming method on basic mapping material in improving geography learning outcomes. This study uses quantitative research with experimental methods. This study uses a quasi-experimental research design, namely a method to determine cause and effect relationships. The sample of this study amounted to 30 people, with data collection techniques through tests and documentation. The statistical tests of this study include normality tests, homogeneity tests, N-Gain tests, and hypothesis tests. Based on the results of the analysis, it can be concluded that the Round Robin Brainstorming learning model is proven to be more effective than conventional learning models in improving geography learning outcomes. This is proven in the experimental class where the N-gain value is 76.36%, included in the "effective" category, while the control class obtained a value of 42.42%, included in the "less effective" category. Independent Sample Test, the significance level value is 0.000<0.05, so it can be concluded that Ho is rejected and Ha is accepted, meaning that the Round Robin Brainstorming learning model is effective in improving student learning outcomes.